2019
DOI: 10.3126/ijasbt.v7i2.24650
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Ginger Production in Surkhet District, Nepal

Abstract: Ginger is a high value crop belongs to family Zingiberaceae. Ginger has multiple health benefits and can be easily grown in mid-hill regions of Nepal. The major challenge is the limited availability of information on factors affecting ginger yield. The objective of this project was to analyze different factors influencing ginger production. The study was conducted in Surkhet district of Nepal in 2018. A total of 100 farmers (60 and 40 from Barahtal and Chingad rural municipalities respectively) were selected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
7
1
Order By: Relevance
“…Among that average land, area under ginger cultivation was 0.13 ha (16.25% of average land holding size) with productivity 14.44 ton/ha. In a study done by Mahat (2019); the average productivity of ginger was found to be 22.07 ton/ha which is more than the productivity seen in this study.…”
Section: Production Situationcontrasting
confidence: 66%
“…Among that average land, area under ginger cultivation was 0.13 ha (16.25% of average land holding size) with productivity 14.44 ton/ha. In a study done by Mahat (2019); the average productivity of ginger was found to be 22.07 ton/ha which is more than the productivity seen in this study.…”
Section: Production Situationcontrasting
confidence: 66%
“…Similarly, Shrestha et al (2010) and Atreya (2005) also reported that a very low number of Nepalese farmers have heard about IPM techniques. Provision of farmer training and extension services could solve pesticide problems along with enhanced farm production (Mahat et al, 2019). IPM techniques emphasize the physical and biological control of pests along with no or minimal use of chemical pesticides.…”
mentioning
confidence: 99%
“…In that fi nding, education is related to the ability to produce and how to improve the production of ginger [20]. In contrast an education was not factor according to the study from Nepal but it stated as it has positive correlation with production [21]. The study from Nigeria based on the sample size of 100 farmers, by using the stochastic frontier production function showed that fertilizer was a signifi cant determinant of farm output [19].…”
Section: Resultsmentioning
confidence: 99%
“…with [21]. This means there was a strong positive relationship between farm size and ginger production.…”
Section: Model Diagnosticsmentioning
confidence: 87%